Fluorescence emission enhancement of poly(phenylacetylene) via thermal annealing. (4th March 2017) - Jin, Young-Jae; Kim, Hyojin; Hwang, Dong-Yeon; Teraguchi, Masahiro; Kaneko, Takashi; Aoki, Toshiki; Kwak, Giseop
ABSTRACT: Both cis - and trans -rich poly[ p -(trimethylsilyl)phenylacetylene]s (PTM-SPAs) were synthesized using [Rh(norbornadiene)Cl]2 -TEA (TEA: triethylamine) and WCl6 -Ph4 Sn as catalysts, respectively. The Rh-based cis -rich polymer exhibited a remarkable fluorescence (FL) emission enhancement after thermal annealing (heating at 200°C in N2 atmosphere for 1 min), while the pristine polymer was almost entirely non-emissive. NMR and Raman spectroscopic studies clarified the occurrence of irreversible cis - trans isomerization under thermal annealing and suggested that the FL emission increased with an increase in the trans content of PTMSPA. Computer simulations of 12-mer model compounds clarified that the FL emission is a result of intramolecular excimers formed from side-on π-stacking of phenyl groups, which is possible only along the backbone of the trans -based polymer.